Testing the effectiveness of two lucid dream induction methods: a four-week diary study - Schredl, Michael (International journal of dream research, 2025)
Lucid dreams (being aware that one is dreaming while still dreaming) can be a lot of fun. As lucid dreams occur relatively rare spontaneously, researchers investigated possible techniques to increase lucid dream frequency. In the present study, 81 persons (59 women, 22 men) were assigned to one of two induction techniques that should be practiced for four weeks. The findings indicate that neither the reality testing technique nor the autosuggestion technique showed a significant increase in lucid dream frequency. The direct comparison of the two induction techniques yielded a significant difference (medium effect size) at first, with the reality testing method superior to the autosuggestion method. However, this group difference was almost completely explained by differences in pre-study lucid dream frequency between the two groups. Overall, the main factor whether a person experienced lucid dreams during the study period was the frequency of lucid dreams the person had prior to participating in the study. The question of whether everyone can learn to have lucid dreams is still open to debate.
Gesehen am 08.10.2025